Exploration of the Quorum-Quenching Mechanism in Pseudomonas nitroreducens W-7 and Its Potential to Attenuate the Virulence of Dickeya zeae EC1 - Zhang, Wenping; Fan, Xinghui; Li, Jiayi; Ye, Tian; Mishra, Sandhya; Zhang, Lianhui; Chen, Shaohua (Frontiers in Microbiology, 2021)
Quorum quenching (QQ) is a novel, promising strategy that opens up a new perspective for controlling quorum-sensing (QS)-mediated bacterial pathogens. QQ is performed by interfering with population-sensing systems, such as by the inhibition of signal synthesis, catalysis of degrading enzymes, and modification of signals. In many Gram-negative pathogenic bacteria, a class of chemically conserved signaling molecules named N-acyl homoserine lactones (AHLs) have been widely studied. AHLs are involved in the modulation of virulence factors in various bacterial pathogens including Dickeya zeae. D. zeae is the causal agent of plant-rot disease of bananas, rice, maize, potatoes, etc., causing enormous economic losses of crops. In this study, a highly efficient AHL-degrading bacterial strain W-7 was isolated from activated-sludge samples and identified as Pseudomonas nitroreducens. Strain W-7 revealed a superior ability to degrade N-(3-oxododecanoyl)-L-homoserine lactone (OdDHL) and completely degraded 0.2 mmol/L of OdDHL within 48 h. Gas chromatography–mass spectrometry (GC-MS) identified N-cyclohexyl-propanamide as the main intermediate metabolite during AHL biodegradation. A metabolic pathway for AHL in strain W-7 was proposed based on the chemical structure of AHL and intermediate products. In addition to the degradation of OdDHL, this strain was also found to be capable of degrading a wide range of AHLs including N-(3-oxohexanoyl)-L-homoserine lactone (OHHL), N-(3-oxooctanoyl)-L-homoserine lactone (OOHL), and N-hexanoyl-L-homoserine lactone (HHL). Moreover, the application of strain W-7 as a biocontrol agent could substantially attenuate the soft rot caused by D. zeae EC1 to suppress tissue maceration in various host plants. Similarly, the application of crude enzymes of strain W-7 significantly reduced the disease incidence and severity in host plants. These original findings unveil the biochemical aspects of a highly efficient AHL-degrading bacterial isolate and provide useful agents that exhibit great potential for the control of infectious diseases caused by AHL-dependent bacterial pathogens.